The Effect of Diaphragmatic Breathing Exercise Technique on Increasing Oxygen Saturation in Asthma Patients - Ni Komang Satia Salini; Ni Made Dwi Yunica Astriani; Putu Indah Sintya Dewi; Ni Ketut Putri Marthasari (JOSING: Journal of Nursing and Health, 2023)
This study aims to determine the effect of the Diaphragmatic Breathing Exercise technique on increasing oxygen saturation in asthma patients. This study uses a quantitative approach with the type of Pre-Experimental One Group Pre-Test and post-test research with the Paired Sample T-Test. The results showed that administering the Diaphragmatic Breathing Exercise technique can increase oxygen saturation in asthma patients before and after the intervention. The oxygen saturation value before being given the Diaphragmatic Breathing Exercise technique showed that the frequency of oxygen saturation of respondents was in the range of 90%-94%, amounting to 38 people (67.9%) with the category of mild hypoxemia and in the field of 75%-89% amounting to 18 people (32.1%) with the type of moderate hypoxemia with an average value of 89.61%. The oxygen saturation value after being given the Diaphragmatic Breathing Exercise technique showed that the frequency of oxygen saturation in the range of 95%-100% amounted to 49 people (87.5%) with the standard category and in the field of 90%-94% amounted to 7 people (12.5%) with the type of mild hypoxemia with an average value of 96.61%. It can be concluded that the Diaphragmatic Breathing Exercise technique affects increasing oxygen saturation in asthma patients. Keywords: Asthma, Diaphragmatic Breathing Exercise, Oxygen Saturation